Stylosines A and B, anti-inflammatory diterpenoid alkaloids from Aconitum stylosum. Issue 42 (16th October 2020) - Shu, Yan; Wang, Jia-Peng; Cai, Xue-Yun; Li, Xiao-Lan; Hu, Jun-Tao; Sun, Cheng-Tong; Cai, Le; Ding, Zhong-Tao
Abstract: Two previously undescribed seco-type C19 -diterpenoid alkaloids, stylosines A and B (1 –2 ), which possess an unprecedented opened D ring by the C(15) –C(16) broken bond forming a five-membered C(15) −O–C(14) lactone ring, together with 14 known diterpenoid alkaloids were isolated from the roots of Aconitum stylosum (Ranunculaceae). Compound 1 is the first reported C19 -diterpenoid alkaloid with an α -orientation at H-13. Their structures were determined by extensive spectroscopic analyses, NMR calculations and DP4+ analysis. A plausible biosynthetic pathway of the undescribed compounds was proposed. Compounds 1 and 2 showed significant inhibitory activity against the production of inflammatory cytokines (interleukin 1 β, cyclooxygenase-2, and tumor necrosis factor α ) in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages. Compounds 1 and 2 exhibited antibacterial activity against Staphylococcus aureus with MIC values of 2.00 and 32.00  μ g/mL, respectively. Graphical abstract: Image 1 Highlights: Stylosines A and B (1 –2 ), which possess an unprecedented opened D ring by the C(15) –C(16) broken bond forming a five-membered C(15) −O–C(14) lactone ring . Compound 1 is the first reported C19 -diterpenoid alkaloid with α -orientation at H-13. Compounds 1 and 2 showed significant anti-inflammatory effects. Compounds 1 and 2 exhibited antibacterial activity against Staphylococcus aureus.